Caesium diuranium hexatelluride - Mesbah, Adel (International Union of Crystallography, 2012)
Single crystals of CsU(2)Te(6) were synthesized from the reaction of U, Te, and Cs(2)Te(3) at 1273 K. CsU(2)Te(6) crystallizes in the space group Cmcm in the CsTh(2)Te(6) structure type. The asymmetric unit comprises one U (site symmetry m2m), one Cs (m2m; half-occupancy) and two Te atoms (m.. and m2m). The structure of CsU(2)Te(6) consists of infinite [U(2)Te(6)] layers perpendicular to [010] separated by Cs atoms. There are infinite Te—Te—Te linear chains along [001].